2011
DOI: 10.1097/smj.0b013e31821ec7cc
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Idiopathic Neutrophilia

Abstract: Cigarette smoking and obesity are confirmed as factors associated with CIN and may be causative. CIN is unlikely to develop into a clinically recognizable myeloproliferative neoplasm other than CML. Cost-effective guidelines for the diagnostic evaluation of neutrophilia in otherwise healthy patients are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We know however that inflammatory markers have a temporal relationship to smoking,25 and this might explain the delay in CIN presentation. Cigarette smoking was suggested as a potential cause for this condition in our patient after an extensive diagnostic analysis excluded other possible conditions or intake of medications such as corticosteroids and lithium which are associated with neutrophilia 9. Despite the use of medically-approved methods, the patient failed to quit smoking.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…We know however that inflammatory markers have a temporal relationship to smoking,25 and this might explain the delay in CIN presentation. Cigarette smoking was suggested as a potential cause for this condition in our patient after an extensive diagnostic analysis excluded other possible conditions or intake of medications such as corticosteroids and lithium which are associated with neutrophilia 9. Despite the use of medically-approved methods, the patient failed to quit smoking.…”
Section: Discussionmentioning
confidence: 86%
“…Chronic idiopathic neutrophilia (CIN) is a condition characterized by asymptomatic elevation of white blood cells (WBCs) and neutrophil count that persists for years without any underlying disease 9. Smoking has been implicated as a cause of this condition,9,10 and leukocyte count is a predictor of future cardiovascular events 11,12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally focused history and physical examination, complete blood count, and chemistry profile must be repeated at 2, 6, and 12 months and annually thereafter. Additional testing, including PCR or FISH techniques for bcr-abl, JAK-2 mutational testing, erythropoietin levels, and bone marrow examination with cytogenetics, must be warranted for patients suspected of having a myeloproliferative neoplasm [3]. …”
Section: Discussionmentioning
confidence: 99%
“…CIN is rarely mentioned in scientific literature and in academic books of hematology; only few words are dedicated to this topic. The most extensive contribution to the definition of CIN is a recent study by Weir and colleagues who reported a cohort of 134 adult patients with leukocyte count between 11000 and 40000/mm 3 without other clinical or hematologic comorbidities, except for the fact that many of them were smokers [3]. …”
Section: Introductionmentioning
confidence: 99%